PENGOLAHAN LIMBAH MINYAK JELANTAH MENJADI LILIN AROMATERAPI BERNILAI JUAL DALAM GERAKAN 3R - Kumoro, Imanuel Dimas Cahyo; Trisnapradika, Gustina Alfa; Rahma, Khalida Nur; Kartikadarma, Etika (Pusat Penelitian dan Pengabdian Masyarakat, 2024)
Indonesia is one of the largest waste-contributing countries in the world. This is no exception in Kelurahan Bandarharjo which has a large population so that household waste production is directly proportional to the population. The processing of household waste needs special attention, both from the household scale to the national scale. So far, household waste has only been collected at a TPS and ends up piled up in a TPA. This cannot continue because these piles of rubbish can become a source of pollution and disease for the community. Used cooking oil or jelantah is a type of waste that must be found in every household. So the service team carried out outreach activities and demonstrations on the processing used cooking oil waste or jelantah which was then processed into aromatherapy candles to turn waste into high-value selling products.. The method used in this service is in the form of socialization and demonstrations carried out in one day. As a result, the 3R (Reduce, Reuse, Recycle) movement provides an increase in public knowledge in managing the cleanliness of the earth. The team hopes that this training can also be disseminated in the surrounding district.